Iklim Komunikasi Organisasi dalam Analisis Keberlanjutan Status Karyawan Kontrak di Sektor Ritel - Ni Wayan Eka Wardani; Rieka Yulita Widaswara; Ida Bagus Benny Surya Adi Pramana (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The increasing use of contract-based employment in the retail sector has raised concerns regarding job insecurity, which may affect employees’ motivation and the sustainability of employment relationships. In this context, internal organizational communication plays an important role in shaping employees understanding of performance evaluation processes and contract renewal opportunities. This study aims to analyze internal organizational communication practices and their relation to the sustainability of contract employees’ employment status at CV. Niaga Multi Ritel. A qualitative descriptive approach was employed in this study. Data were collected through in-depth interviews with contract employees, direct supervisors, and management representatives, supported by observation and document analysis. Informants were selected using purposive sampling based on their involvement in communication and performance evaluation processes. The findings indicate that organizational communication within the company is predominantly informal, unstructured, and not conducted on a continuous basis, particularly in relation to performance feedback and the clarity of evaluation indicators. This condition contributes to the emergence of perceived job insecurity among contract employees. Conversely, more open and transparent communication helps enhance employees’ understanding of work expectations and employment continuity opportunities. This study highlights that organizational communication plays a strategic role in supporting the sustainability of contract employees’ employment status and should therefore be managed more systematically.